Teaching An Inclusive Education in EFL Setting: A Phenomenological Study - Padmadewi, Ni Nyoman; Artini, Luh Putu; Sukadana, I Made Sukma Adisetiawan (The Art of Teaching English as a Foreign Language (TATEFL), 2024)
Inclusive education is highly essential to provide equitable quality education and is included as one of the courses in the curriculum of the English Language Education Study Program of Ganesha University of Education since the year 2021. In spite of having been a part of the curriculum for three years, no research was conducted on how the course is implemented. The purpose of this study was to investigate the strategies used by the lecturer to teach the course. The research was in the form of a phenomenological design. There were 31 students and one lecturer involved in the study. The data was collected for one semester in 2023, and the techniques of data collection were observation, deep interviews, and document study. The data were analyzed qualitatively. The findings show that in one semester, the lecturer applied a strategy of teaching and learning process abbreviated as GROWFIT, which stands for guide (orientation), research (independent study), observe (to learn from real-world environments), workshop (presenting ideas in a workshop-style setting), feedback (engaging in discussion and providing feedback), improve (reviewing and refining skills based on feedback), and think (synthesizing knowledge in final projects and showcasing critical thinking). The implementation of GROWFIT yields positive perspectives from the students, and all the students passed the course. It is implied that the GROWFIT model implemented was essentially effective in enhancing students' understanding about inclusive education.